The impact of climate change on piracema and the sustainability of aquatic resources (Research, Society and Development, 2024)
The impact of climate change on piracema and the sustainability of aquatic resources are essential topics in riverine conservation. Piracema refers to the reproductive period of fish, during which they masse migrate to specific locations for spawning. Thus, climatic variations altering environmental conditions directly affect this vital cycle. This study addresses the implications of these changes, emphasizing the vulnerability of the mentioned phenomenon and delineating its repercussions on aquatic biodiversity. Through scientific articles and academic works, it was analyzed that temperature elevation, irregular rainfall patterns, and extreme climatic events can compromise the migration and successful reproduction of fish. Therefore, conservation strategies, including community engagement, infrastructure adaptation, and continuous scientific research, are essential to mitigate these impacts. The sustainability of aquatic resources depends on a delicate balance between preserving piracema and active participation in adaptive management, fostering a healthy coexistence between riverine ecosystems and human communities.